Binary search algorithm as maximum power tracking technique for photovoltaic system under partial shaded conditions - Meng Chung, Tiong; Hamdan, Daniyal; Mohd Herwan, Sulaiman; Mohd Shafie, Bakar (IEEE, 2018)
This paper presents an approach to determine the maximum power point (MPP) in photovoltaic (PV) system under partial shaded conditions using Binary Search Algorithm (BSA). The BSA perform MPP tracking by changing the search boundaries to eliminate the region where the MPP cannot lie. In this study, the BSA and particle swarm optimization (PSO) based MPPT were developed in Matlab Simulink with a DC/DC boost converter. Both algorithms were simulated under ten different test cases of partial shading conditions to study the accuracy, speed and tracking efficiency. BSA exhibits a fast convergence with zero steady state oscillation along with the capability of performing MPP tracking under partially shaded PV system.